Processo de filiação: um estudo de adoção de dois irmãos maiores - Silva, Carolina Lemos da (Universidade do Vale do Rio dos Sinos, 2011)
The purpose of this Master thesis is twofold: to explore the process of becoming a father, a mother and a son/daughter in a process of adoption of older siblings, and to interpret how the parent-children relationship is developed. Using qualitative methodology and psychoanalytical theory, a case study is presented and discussed, providing both parents’ and kids’ perspectives in the process of affiliation. Within the parental perspective, the specific objectives are to understand the motivation and desires in the adoption process; to identify the fears, fantasies and grieves related to this process; and to examine the parent-children identification process in a longitudinal follow-up of eight months (May to December 2010). Regarding the children’s perspective, the specific objectives are to identify characteristics on the stage of family intimacy and their fears in the process. Data was obtained in 14 meetings over a period of 5 months. The procedures used were family drawing projective test, individual diary, pictures, open-ended clinical interviews, anamnesis interview and documental research – the investigation about the process of removing the kids from their original family. Participants were two siblings, a 10 year-old boy and a 3 years and 8 month girl, who were in an institution to be adopted, and a couple who was allowed to adopt by the official state agency. Data analysis was done through the psychoanalytical concepts of Desire, Non-Desire, Narcissism, Identification, Familiar Romance and Symbolic Affiliation. We enhanced and assisted this adoption process through lessening the difficulties, orienting and clarifying questions regarding the familiar intimacy stage, and helping in the development of affiliation.
Keywords: Adoção; Pai; Mãe; Filho; Irmãos maiores; Psicanálise; Identificação; Romance familiar; Filiação; Adoption; Father; Mother; Children; Older sibling; Psychoanalysis; Identification; Familiar romance; Affiliation; ACCNPQ::Ciências Humanas::Psicologia